Rootstock Influences on Health and Growth Following Candidatus Liberibacter asiaticus Infection in Young Sweet Orange Trees - Kim D. Bowman; Ute Albrecht (Agronomy, 2020)
Health, growth, fruit production, and fruit quality of citrus crops are severely affected by tree infection with Candidatus Liberibacter asiaticus (CLas) and subsequent development of the disease huanglongbing (HLB). The use of HLB-tolerant rootstocks is one strategy that is used to ameliorate the effects of HLB in commercial production. Although there is a clear long-term rootstock effect to improve tree performance, such field trials take many years for establishment and evaluation, and this long time-period is very limiting to expeditious evaluation of new rootstocks. In this study, we have conducted a 50-week greenhouse experiment to evaluate rootstock influences on Valencia sweet orange tree response to CLas infection. The infection of trees with CLas reduced scion and rootstock growth, increased leaf yellowing, and reduced the number of leaves per tree and leaf area, regardless of rootstock. There were clear rootstock influences on some traits during the 50-week study. In general, infected trees on US-942 rootstock had lower CLas root titers, less reduction of the number of leaves, less reduction of leaf area, and less leaf yellowing, as compared with some of the other rootstocks. The 50-week greenhouse evaluation method provided results that corresponded well with results from long-term field testing, indicating this may be a useful tool to accelerate evaluation and selection of new rootstocks, as well as in testing other HLB management strategies.